1189 Recruiting, Training, And Implementing Sleep Health Educators In Community-based Research To Improve Sleep Health. (27th May 2020) - Aird, C; Seixas, A; Moore, J; Nunes, J; Gyamfi, L; Garcia, J; Blanc, J; Williams, N; Zizi, F; Jean-Louis, G
Abstract: Introduction: Adherence to OSA assessment and treatment is low among racial/ethnic minorities, particularly among blacks. Navigating patients along the continuum of care from assessment to treatment adherence requires motivation, social support, and self-efficacy. Previous studies indicate that community health educators can provide motivation, social support, and skills to patients to better navigate the complex OSA care continuum. However, recruiting, training, and implementing sleep health educators in clinical or research settings is complex. For the current study, we describe how we recruit, train, and implement sleep health educators in research and clinical settings and assess what makes a sleep health educator successful. Methods: We recruited and trained twenty-five self-identified black sleep health educators for a randomized clinical trial (R01MD007716) focused on increasing OSA assessment and treatment adherence among blacks. During recruitment, we assessed key personality attributes that translate to being an effective sleep health educator, via behavioral and personality surveys, focused groups, and process forms filled out by educators. Sleep health educators underwent an 8-week training program on sleep health and motivational interviewing. In order to be certified, sleep health educators had to pass a written and scenario-based assessment. During the implementation phase of the trial, we assessed how many interviews each health educator conducted and whether individual characteristics were related to how many interviews. Results: Of the trained educators, 80% were female, ranging from 25 to 58 years old. They all completed at least high school. All educators rated the program highly and were very satisfied with dispensing tailored sleep health education. Educators who displayed the highest knowledge about sleep health, provided frequent emotional and strategic support, committed to helping their assigned participants, and who rated their rapport highly with their assigned participants were most effective in getting their participant to adhere to OSA assessment and treatment. Conclusion: Sleep health educators can be vital to increasing OSA assessment and treatment adherence among blacks. In order to ensure success, sleep health educators must undergo a thorough recruitment, training, and implementation and dissemination process. Support: K01HL135452, R01MD007716, R01HL142066, K01HL135452, and K07AG052685